Foot Anthropometry Measures in Relation to Treatment in Patients with Rheumatoid Arthritis: A Longitudinal Study - Gamez Guijarro, Maria; Reinoso-Cobo, Andrés; Perez Galan, María José; Ortega-Ávila, Ana Belén; Ramos-Petersen, Laura; Torróntegui-Duarte, Marcelino; Gijón-Noguerón, Gabriel; Lópezosa-Reca, Eva (MDPI, 2024)
Approximately 90% of patients with arthritis exhibit forefoot deformities, including deformities within the metatarsophalangeal and proximal interphalangeal joints. Current pharmacological treatment with Disease Modifying Antirheumatic Drugs (DMARDs) consists of two groups: synthetic drugs (sDMARDs) and biological drugs (bDMARDs). The objective of our study was to investigate foot anthropometry changes in RA patients based on the administered treatment over a five-year period Method: A longitudinal analysis was conducted with RA patients who were grouped based on their pharmacological treatment. The pharmacological treatment groups were categorized into (I) methotrexate (MTX), (II) MTX plus biological treatments (including all variables), (III) biological treatment alone, and (IV) a miscellaneous group comprising patients with diverse treatments, including patients for whom various drugs had failed or who had not achieved remission with pharmacological treatment. For the anthropometric measurements, a foot measurement platform validated by McPoil et al. was used. Post hoc analyses with Bonferroni correction were performed to identify pairwise differences between the treatment groups while controlling for Type I errors due to multiple comparisons. Results: In the period from 2018 to 2023, significant changes were observed in several foot measurements. For instance, the MTX group showed a statistically significant increase in left heel width (p = 0.026). The MTX group experienced a slight increase in left foot length, while the Biologics and MTX + Bio groups exhibited more substantial increases in both maximum medial arch height and midfoot width. Conclusions: Different RA treatments can have a significant impact on foot structure over a five-year period, showing notable changes in heel width and overall foot morphology. Combined treatments with MTX and biologics potentially offer better management of RA.
Keywords: Pies - Anomalías y malformaciones; Deformity; Treatments; Rheumatoid arthritis; Foot